Evaluation of concrete tensile strength as a function of temperature. (25th April 2022) - van der Merwe, Johann Eduard
Highlights: Some expressions proposed to date perform well also beyond their scope of development. A more practical expression should rely on compressive strength as reference parameter. A single expression for various concrete types is adequate and appropriate. Alternative expressions are proposed to estimate high-temperature tensile strength. Abstract: A practical and accurate expression is proposed in this paper to evaluate concrete tensile strength as a function of temperature. To this purpose, a database comprising many well-documented experimental results was prepared and a number of tests were performed by the Author, to formulate and validate the proposed expression, considering both normal and high strength concretes. Several expressions proposed elsewhere in literature were checked as well. In the formulation of the proposed expression, the benefits coming from the introduction of multiple predictor variables were investigated, as well as those resulting from simple linear regression models. Many of the expressions are shown to perform well, even beyond the limits characterising each formulation. Finally, the database and the linear regression models clearly show that concrete grade and mix properties play no significant role in the reduction of concrete tensile strength with increased temperature.